Activation of the FGFR1 signalling pathway by the Epstein–Barr virus‐encoded LMP1 promotes aerobic glycolysis and transformation of human nasopharyngeal epithelial cells. Issue 2 (3rd August 2015) - Lo, Angela Kwok‐Fung; Dawson, Christopher W; Young, Lawrence S; Ko, Chuen‐Wai; Hau, Pok‐Man; Lo, Kwok‐Wai
Abstract Non‐keratinizing nasopharyngeal carcinoma (NPC) is closely associated with Epstein–Barr virus (EBV) infection. The EBV‐encoded latent membrane protein 1 (LMP1) is believed to play an important role in NPC pathogenesis by virtue of its ability to activate multiple cell signalling pathways which collectively promote cell proliferation, transformation, angiogenesis, and invasiveness, as well as modulation of energy metabolism. In this study, we report that LMP1 increases cellular uptake of glucose and glutamine, enhances LDHA activity and lactate production, but reduces pyruvate kinase activity and pyruvate concentrations. LMP1 also increases the phosphorylation of PKM2, LDHA, and FGFR1, as well as the expression of PDHK1, FGFR1, c‐Myc, and HIF‐1α, regardless of oxygen availability. Collectively, these findings suggest that LMP1 promotes aerobic glycolysis. With respect to FGFR1 signalling, LMP1 not only increases FGFR1 expression, but also up‐regulates FGF2, leading to constitutive activation of the FGFR1 signalling pathway. Furthermore, two inhibitors of FGFR1 (PD161570 and SU5402) attenuate LMP1‐mediated aerobic glycolysis, cellular transformation (proliferation and anchorage‐independent growth), cell migration, and invasion in nasopharyngeal epithelial cells, identifying FGFR1 signalling as a key pathway in LMP1‐mediated growth transformation. Immunohistochemical staining revealed that high levels of phosphorylated FGFR1 are common in primary NPC specimens and that this correlated with the expression of LMP1. In addition, FGFR1 inhibitors suppress cell proliferation and anchorage‐independent growth of NPC cells. Our current findings demonstrate that LMP1‐mediated FGFR1 activation contributes to aerobic glycolysis and transformation of epithelial cells, thereby implicating FGF2/FGFR1 signalling activation in the EBV‐driven pathogenesis of NPC. Copyright © 2015 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.